PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU DALAM PENANGANAN SAMPAH DI KOTA PEKANBARU PADA TAHUN 2018 - Sepriani, Yulia; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Writing a thesis entitled the waste management by the environmental and cleanliness department of Pekanbaru city in waste handling in the city of Pekanbaru in 2018, waste management in Indonesia is regulated in law number 18 of 2008 concerning waste management. The environmental and sanitation office of Pekanbaru city an SOP ( Standard of service operation) to simplify and clarify the affair of waste management, however so far optimal waste management has not been achieved. As for there are inhibiting factors in waste management itself, namely internal and external factors. This research was conducted at the Department and Cleanliness of Pekanbaru City. The purpose of this study is to describe the flow of waste management by the environmental and cleanliness department of Pekanbaru city in waste management in the city in 2018. The theory used is management theory from Rahardjo Adisasmita, the research method used is descriptive qualitative with interview and documentation data collection techniques the type of data used is secondary data and primary data. The final conclusion of this research is that by using management theory, the implementation of waste management has not been fully implementation with the theory that has been used. Keywords : Management, Trash, Regional Government.